Long term cause specific mortality among 34 489 five year survivors of childhood cancer in Great Britain: population based cohort study. (1st September 2016) - Fidler, Miranda M; Reulen, Raoul C; Winter, David L; Kelly, Julie; Jenkinson, Helen C; Skinner, Rod; Frobisher, Clare; Hawkins, Michael M
Abstract : Objective  To determine whether modern treatments for cancer are associated with a net increased or decreased risk of death from neoplastic and non-neoplastic causes among survivors of childhood cancer. Design  Population based cohort study. Setting  British Childhood Cancer Survivor Study. Participants  Nationwide population based cohort of 34 489 five year survivors of childhood cancer with a diagnosis from 1940 to 2006 and followed up until 28 February 2014. Main outcome measures  Cause specific standardised mortality ratios and absolute excess risks are reported. Multivariable Poisson regression models were utilised to evaluate the simultaneous effect of risk factors. Likelihood ratio tests were used to test for heterogeneity or trend. Results  Overall, 4475 deaths were observed, which was 9.1 (95% confidence interval 8.9 to 9.4) times that expected in the general population, corresponding to 64.2 (95% confidence interval 62.1 to 66.3) excess deaths per 10 000 person years. The number of excess deaths from all causes declined among those treated more recently; those treated during 1990-2006 experienced 30% of the excess number of deaths experienced by those treated before 1970. The corresponding percentages for the decline in excess deaths from recurrence or progression and non-neoplastic causes were 30% and 60%, respectively. Among survivors aged 50-59 years, 41% and 22% of excess deaths were attributable to subsequent primary neoplasms and circulatory conditions, respectively, whereas the corresponding percentages among those aged 60 years or more were 31% and 37%. Conclusions  The net effects of changes in cancer treatments, and surveillance and management for late effects, over the period 1940 to 2006 was to reduce the excess number of deaths from both recurrence or progression and non-neoplastic causes among those treated more recently. Among survivors aged 60 years or more, the excess number of deaths from circulatory causes exceeds the excess number of deaths from subsequent primary neoplasms. The important message for the evidence based surveillance aimed at preventing excess mortality and morbidity in survivors aged 60 years or more is that circulatory disease overtakes subsequent primary neoplasms as the leading cause of excess mortality.